Status of Geodetic Astronomy at the Beginning of the 21st Century - Hirt, Christian; Burki, B. (University of Hanover, 2006)
At the beginning of the 21st century, a significant technological change took place in geodetic astronomy. The use of digital imaging sensors strongly improved the degree of automation, efficiency and accuracy of methods for the observation of the direction of the plumb line and its vertical deflection. This paper outlines the transition of astrogeodetic techniques and applications from the analogue to the digital era and addresses instrumental developments and recently completed projects. Particular attention is given to Digital Zenith Camera Systemsrepresenting astrogeodetic state-of-the-art instrumentation. Moreover, accuracy issues, present application examples for highly-precise astrogeodetic gravity field determinations and some future applications are described.